PERAN MEDECINE SANS FRONTIERES (MSF) DALAM MENGATASI KRISIS PENGUNGSI DI SUDAN SELATAN - Suci Juita Sari; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research will focus on how MSF play a role in addressing the refugee crisis in southern sudan. Medecine Sans Frontieres (MSF) is an international organization, independent, medical humanitarian which provides emergency assistance to people affected by armed conflict, epidemics, natural disasters and exclusion from healthcare. The conflict in South Sudan in mid-late 2013 caused the displacement of a population of more than 2 million refugees from the beginning of the conflict until 2015 and the spread of infectious diseases.This reseacrh used qualitative explanation method by observing phenomena that occur and based from relevant sources to the issues that discussed. the autor used relevant concepts and theories such as the concept of human security and international organisation theory. and also uses the persepctive of pluralism.This research shows that MSF has a full role to the refugee crisis in South Sudan. This is indicated by all the activities that have been performed Since the conflict and refugee crisis that has been widely reported as well as the emergence of the spread of infectious diseases are life-threatening. Program carried out by MSF in the form of medical assistance, building a cholera treatment center and carry out vaccination campaigns cholera and malaria. Furthermore MSF in collaboration with other agencies in addressing this infectious disease outbreaks.Keywords: Refugee crisis, Medecine Sans Frontieres(MSF), Infectious Diseases, South Sudan